ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. BLUE BIRD Tbk PERIODE 2014-2018 - Zakaria Hamzah, Zeze; Awaliyah, Sarah (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2020)
This study aims to determine the financial performance of PT. Blue Bird Tbk was examined based on analysis using the Economic Value Added (EVA) method during the 2014 – 2018 period. A quantitative approach was used and the study population is also a sample of research is the financial statements of the last five years (2014-2018). Data collection is done by taking documentation from the official website and then analyzed using the EVA method which consists of NOPAT analysis, Invested Capital, WACC, Capital Charges. The results showed that Economic Value Added (EVA) at PT. Blue Bird Tbk in the 2014-2018 period got EVA value < 0 meaning that the company could not create economic value added. This happened because the level of capital costs is higher than the rate of return on operating profits of the company due to new competitors in the form of online transportation.